Improving the quality of forgings based on upsetting the workpieces with concave facets - Markov, Oleg; Zlygoriev, Vitalii; Gerasimenko, Oleksiy; Hrudkina, Natalia; Shevtsov, Serhii (Eastern-European Journal of Enterprise Technologies, 2018)
We propose a forging method for forgings, which implies the upsetting of workpieces with concave facets. A procedure for the theoretical research has been devised aimed at studying the mechanism of closure of artificial axial defects in workpieces. The study was performed based on a finite element method. The key examined parameter was the depth of the concave facets in a workpiece. This parameter varied in the range 0.75; 0.85; and 0.80. The angle of the concave facets was 120°. The results of the theoretical study are the following distributions: deformations, temperatures, and stresses in the body of a workpiece in the process of upsetting the workpieces with concave facets. Based on these parameters, we established an indicator of the stressed state in the axial zone of the workpiece. In order to verify the theoretical results obtained, a procedure for experimental research has been developed. The study was performed using the lead and steel workpieces. The results of the theoretical study allowed us to establish that the effective depth of the concave facets is the ratio of diameters of protrusions and ledges equal to 0.85. At this ratio there occurs the intensive closure of an axial defect. This is due to the high level of compressive stresses when upsetting the workpieces with concave facets. We have established the effective degree of deformation at which the intensive closure of defects takes place. Also established are the distributions of deformations for the cross-section and height of the workpiece, as well as a change in the indicator of the stressed state in the process of upsetting workpieces with concave facets. The closure of axial defects has been confirmed by experimental study using lead and steel samples. The new technique for upsetting workpieces with concave facets has been implemented. The results of ultrasonic testing have allowed us to establish that the obtained parts do not have internal defects, which exceed the requirements of the European standard SEP 1921. Our research has led to the conclusion of the high efficiency of the proposed new method for upsetting workpieces with concave facets, which implies the improvement of quality of the axial zone of large forgings when using a given technique.